Ethylene Participates in the Regulation of Fe Deficiency Responses in Strategy I Plants and in Rice - Lucena, Carlos; Romera, Francisco J.; García, María J.; Alcántara, Esteban; Pérez-Vicente, Rafael (Frontiers in Plant Science, 2015)
Iron (Fe) is very abundant in most soils but its availability for plants is low, especially in calcareous soils. Plants have been divided into Strategy I and Strategy II species to acquire Fe from soils. Strategy I species apply a reduction-based uptake system which includes all higher plants except the Poaceae. Strategy II species apply a chelation-based uptake system which includes the Poaceae. To cope with Fe deficiency both type of species activate several Fe deficiency responses, mainly in their roots. These responses need to be tightly regulated to avoid Fe toxicity and to conserve energy. Their regulation is not totally understood but some hormones and signaling substances have been implicated. Several years ago it was suggested that ethylene could participate in the regulation of Fe deficiency responses in Strategy I species. In Strategy II species, the role of hormones and signaling substances has been less studied. However, in rice, traditionally considered a Strategy II species but that possesses some characteristics of Strategy I species, it has been recently shown that ethylene can also play a role in the regulation of some of its Fe deficiency responses. Here, we will review and discuss the data supporting a role for ethylene in the regulation of Fe deficiency responses in both Strategy I species and rice. In addition, we will review the data about ethylene and Fe responses related to Strategy II species. We will also discuss the results supporting the action of ethylene through different transduction pathways and its interaction with other signals, such as certain Fe-related repressive signals occurring in the phloem sap. Finally, the possible implication of ethylene in the interactions among Fe deficiency responses and the responses to other nutrient deficiencies in the plant will be addressed.